The application of transpiration cooling as a thermal protection system for hypersonic vehicles - Naved, I (2022)
This thesis investigates the application of transpiration cooling to reduce surface heat transfer on hypersonic vehicles. Such vehicles experience high peak heat fluxes and time-integrated heat loads throughout the ascent, re-entry, and cruise phases. The most significant heat fluxes occur at the stagnation point of sharp leading edges, regions of laminar-turbulent transition, or shock-wave boundary layer interactions. Whilst previous and current hypersonic vehicles employ ablation for many of these regions, such thermal protection systems are neither reusable nor suitable for all scenarios. In this work, the performance of transpiration cooling is assessed for a generic flight vehicle. Subsequently, the application of transpiration cooling to laminar and turbulent flows and shock-wave boundary layer interaction regions is assessed experimentally.